Embedded Scalars, Preferred Readings and Prosody: An Experimental Revisit. (18th August 2016) - Franke, Michael; Schlotterbeck, Fabian; Augurzky, Petra
Abstract: The scalar item some is widely assumed to receive a meaning enrichment to some but not all if it occurs in matrix position. The question under which circumstances this enrichment can occur in certain embedded positions plays an important role in deciding how to delineate semantics and pragmatics. We present new experimental data that bear on this theoretical issue. In distinction to previous experimental approaches, we presented sentence material auditorily in order to explicitly control prosodic markedness of the scalar item. Moreover, our experiment sheds light on the relative preferences or salience of candidate readings. The presented data turn out to be unexpected under a traditional Gricean view, but also challenge the idea of disambiguation by logical strength in grammaticalist approaches.